2016
DOI: 10.1016/j.envpol.2016.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution, metabolism and hepatic tissue injury in Chinese lizards (Eremias argus) after a single oral administration of lambda-cyhalothrin

Abstract: a b s t r a c tLambda-cyhalothrin (LCT) is a widely used pyrethroid with neurotoxicity. However, little is known about the toxicokinetics of LCT in reptiles. In this study, the absorption, distribution, metabolism and excretion of LCT in Chinese lizards (Eremias Argus) were determined following a single dose (10 mg kg À1 ) treatment. In the liver, brain, gonads and skin, LCT levels peaked within several hours and then decreased rapidly. However, the concentration of LCT gradually increased in the fat tissue. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 69 publications
(80 reference statements)
2
9
0
Order By: Relevance
“…As the liver is also one of the major organs to accumulate flufenoxuron, the decrease of hepatic index can be attributed to the low degree for detoxification of flufenoxuron in the liver. Similar with the result of flufenoxuron, lizards exposed to pyrethroid pesticides showed significant decrease in the hepatosomatic index (Chang et al, 2016;Chen et al, 2016). In that case, the liver can be considered as an indicator of detoxification ability of lizards.…”
Section: Groupsupporting
confidence: 69%
See 2 more Smart Citations
“…As the liver is also one of the major organs to accumulate flufenoxuron, the decrease of hepatic index can be attributed to the low degree for detoxification of flufenoxuron in the liver. Similar with the result of flufenoxuron, lizards exposed to pyrethroid pesticides showed significant decrease in the hepatosomatic index (Chang et al, 2016;Chen et al, 2016). In that case, the liver can be considered as an indicator of detoxification ability of lizards.…”
Section: Groupsupporting
confidence: 69%
“…In this study, the concentration of diflubenzuron in the fat was the highest while the skin could quickly eliminate or release the diflubenzuron. Our previous study also showed that the level of lambda-cyhalothrin increased with time in the lizard fat but not in the skin (Chang et al, 2016). Several studies have found that diflubenzuron treatment decreased the lipid level in the fat body of mealworms (Khebbeb et al, 1997) and birds (Whitmore et al, 1993).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The elimination of LCT follows the first-order kinetics and most of the dose is eliminated within the first 1−6 h after absorption in lizard tissues. 9 Pyrethroids are rapidly degraded to inactive metabolites, which are excreted primarily through urine. 34 However, the format of LCT metabolites in feces has not been well studied.…”
Section: Gsi (%)mentioning
confidence: 99%
“…It is found to be ubiquitous in treated wastewater and soil. , Uncontrolled use of these insecticides resulted in their entry into the food chain, thereby causing toxicity to different organism systems. Compared with dermal exposure, oral and inhalation result in faster systemic exposure. , Because of its lipophilic properties, pyrethroids tend to deposite in the fat of lizard, rat, and pig. Pyrethroids are demonstrated to be accumulated in fish tissues. , However, the body burden of pyrethroids in terrestrial animals has been seldomly studied.…”
Section: Introductionmentioning
confidence: 99%